Rotatable serial co-sputtering of doped titania. (April 2015) - Sittinger, V.; Pflug, A.; Dewald, W.; Jung, S.; Britze, C.; Kaiser, A.; Werner, W.; Szyszka, B.; Bräuer, G.
Abstract: Serial co-sputtering is an extension of conventional magnetron sputtering: it utilizes cylindrical primary rotating sputter sources within a metallic or reactive sputtering process. With one or more auxiliary sputter sources the surface of the primary sputter target is simultaneously coated with additional elements. In the primary sputtering process, these elements get implanted and mixed into the primary target material leading to production of multi-component films. In this paper we use an installation of this technology called "Megatron™", which involves an effective gas separation between primary and auxiliary chamber volumes. With this setup, we fabricated TiO2 :W and TiO2 :Nb layers by using a rotating Titania target as primary source and planar W and Nb targets as auxiliary sources, respectively. In both cases the so called sputter yield amplification effect (SYA) was demonstrated: Within the TiO2 matrix the heavier element e. g. tungsten keeps the sputter cascade close to the target surface and thus significantly enhances the sputter rate. Additionally, by niobium doping in combination with a post-deposition annealing it is possible to get TiO2 :Nb layers with tailored Nb composition as conductive transparent oxides (TCO). Due to the independent power control of the secondary target the tungsten and niobium concentration can easily be optimized. We present doping series for optimizing either the SYA effect for TiO2 :W or the effect of a transparent conductive TCO for TiO2 :Nb. With tungsten doping we achieved an enhancement of more than twice the DC sputter rate. With niobium doping and a post-deposition annealing step (350 °C) we reach resistivity values of about 1.2 × 10 −3 Ωcm. Highlights: Serial co-sputtering of doped titania. Doping control of metal oxides. Sputter yield amplification (SYA) with tungsten doped TiO2 . Sputter rate enhancement due to SYA of more than a factor of two. Niobium doped TiO2 as high refractive index TCO.